2016
DOI: 10.1097/qad.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Functional screening of guide RNAs targeting the regulatory and structural HIV-1 viral genome for a cure of AIDS

Abstract: Objective There is an urgent need for the development of HIV-1 genome eradication strategies that lead to a permanent cure for HIV-1/AIDS. We previously reported that 4 guide RNAs (gRNAs) targeting HIV-1 long terminal repeats (LTR) effectively eradicated the entire HIV-1 genome. In this study, we sought to identify the best gRNAs targeting HIV-1 LTR and viral structural region and to optimize gRNA pairing that can efficiently eradicate the HIV-1 genome. Design Highly specific gRNAs were designed using bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 68 publications
(56 reference statements)
2
85
0
Order By: Relevance
“…CRISPR/Cas9 can be used either to disrupt the integrated HIV-1 provirus or the cellular genes that are required for productive HIV-1 infection. For example, CRISPR/Cas9 facilitates the excision of HIV proviral DNA segments in several different cell types including CD4+ T-cells and by targeting the flanking HIV-1 LTR sequences, complete excision of proviral DNA can be effected (Ebina et al, 2013; Hu et al, 2014; Kaminski et al, 2016b; Yin et al, 2016). This approach has been demonstrated to be effective in cleaving HIV proviral DNA in latently-infected cells in HIV-infected humanized Bone marrow-Liver-Thymus (hu-BLT) mice (Yin et al, 2017).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR/Cas9 can be used either to disrupt the integrated HIV-1 provirus or the cellular genes that are required for productive HIV-1 infection. For example, CRISPR/Cas9 facilitates the excision of HIV proviral DNA segments in several different cell types including CD4+ T-cells and by targeting the flanking HIV-1 LTR sequences, complete excision of proviral DNA can be effected (Ebina et al, 2013; Hu et al, 2014; Kaminski et al, 2016b; Yin et al, 2016). This approach has been demonstrated to be effective in cleaving HIV proviral DNA in latently-infected cells in HIV-infected humanized Bone marrow-Liver-Thymus (hu-BLT) mice (Yin et al, 2017).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…In principle, multiplex gRNAs can be employed so that the chance of generating escape mutants can be greatly reduced, since the probability of viable mutations occurring at multiple sites is much less than for a single site. Also, if the multiplex gRNAs are designed in such a way as to produce DNA breaks resulting in a large section of DNA being deleted, this will permanently prevent escape mutations from occurring (Hu et al, 2014; Kaminski et al, 2016a,b; Yin et al, 2016, 2017). Some Cas9 variants, e.g., Cpf1, cleave at a site that is outside the target sequence so that InDel mutations introduced at the cleavage site by NHEJ will not prevent further cleavage (Zetsche et al, 2015).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…CRISPR/Cas9 allows the excision of segments of integrated proviral DNA in different latently infected cell types by targeting sequences within the HIV-1 long terminal repeat (LTR) flanking the provirus and allowing complete provirus excision [2022, 2426]. These experiments were performed with T cells [20], microglia, promonocytic T cells [21], primary CD4+ T-cells cultured ex vivo [22], induced pluripotent stem cells [24], HEK293T cells [25], and Jurkat cells [26], indicating that the ability of CRISPR/Cas9 to excise HIV provirus is not restricted by cell-type–specific factors. While the fate of the eliminated DNA arising after excision of segments of integrated proviral DNA is not known for certain, we tend to think that after excision from the genome, it will be degraded.…”
Section: Application To Human Virusesmentioning
confidence: 99%
“…Alternatively, if two gRNAs produce DNA breaks, allowing excision of a large section of DNA, this will permanently prevent the occurrence of escape mutations, as shown in Fig 1. Several studies have demonstrated the strong suppression of HIV-1 using a multiplex approach [2125]. Table 1 summarizes recent studies [5275] on the use of CRISPR/Cas9 technology for editing several human viruses using single and multiplex gRNAs, resulting in the introduction of InDels and/or excision of the segment of the viral genome.…”
Section: Strategies To Combat Viral Escapementioning
confidence: 99%
“…They designed sgRNAs for LTR region, resulting in a remarkable removal and eradication of proviral genome integrated in host genome . Similarly, several studies demonstrated excision and elimination of integrated HIV genome by the CRISPR/Cas9 system in different HIV‐1 latent reservoir cells . Moreover, removing of the integrated HIV genome in in vivo has been demonstrated using transgenic mice and rats models .…”
Section: Introductionmentioning
confidence: 99%